2018
DOI: 10.20537/2076-7633-2018-10-4-445-460
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the movement of the body using internal masses in a viscous liquid

Abstract: This article is devoted to the study of self-propulsion of bodies in a fluid by the action of internal mechanisms, without changing the external shape of the body. The paper presents an overview of theoretical papers that justify the possibility of this displacement in ideal and viscous liquids.A special case of self-propulsion of a rigid body along the surface of a liquid is considered due to the motion of two internal masses along the circles. The paper presents a mathematical model of the motion of a solid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…This paper is devoted to the development and experimental investigations of a prototype of an aquatic robot actuated by rotating a rotor installed inside a shell with a special form. The development of the prototype of an aquatic robot is based on the results of studies of simpler models of robots moving on the surface of a fluid [1][2][3][4]. The research results obtained in these studies have not only confirmed that bodies with asymmetric form are capable of moving on the surface of a fluid by changing the internal angular momentum or changing the position of the center of mass, but also demonstrated agreement between theoretical and experimental results.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…This paper is devoted to the development and experimental investigations of a prototype of an aquatic robot actuated by rotating a rotor installed inside a shell with a special form. The development of the prototype of an aquatic robot is based on the results of studies of simpler models of robots moving on the surface of a fluid [1][2][3][4]. The research results obtained in these studies have not only confirmed that bodies with asymmetric form are capable of moving on the surface of a fluid by changing the internal angular momentum or changing the position of the center of mass, but also demonstrated agreement between theoretical and experimental results.…”
Section: Introductionmentioning
confidence: 83%
“…For example, in recent experimental investigations of resistance forces for a flat shovel, a linear dependence on the logarithm of the linear velocity of motion has been obtained, and the moment of resistance depends linearly on the angular velocity [17], although the velocities of motion were low. For bodies having nonplanar form (the form of an ellipse or airfoil form), the motion was described using the quadratic dependences of the resistance forces on the velocity of motion [1,3,4].…”
Section: Equations Of Motionmentioning
confidence: 99%
“…This energy is calculated using relations (1, 3-5). Right-hand sides of (10) are calculated using formulas (2,(6)(7)(8)(9). Left-hand sides can be written down as follows:…”
Section: Equations Of Motion and The Control Lawmentioning
confidence: 99%
“…During such motion, the center of mass of the robot moves along a serpentine trajectory. This effect is taken as a basis of a vibrational robot 8 with two controlled internal eccentric weights. Apart from the difference in coefficients of added masses corresponding to the two axes of symmetry of the body, this robot uses for propulsion the considerable difference between the values of the hydrodynamic drag along these two axes of symmetry (which is due to the presence of a keel).…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to modeling the motion of rigid bodies in a viscous fluid, the most detailed description of the system dynamics can be obtained by using a joint numerical solution of the Navier-Stokes equations and equations of body motion [15,36,44]. Such an approach involves rather laborious calculations, but turns out to be useful in constructing various finite-dimensional models of body motion in a fluid [5,19,31]. A qualitative investigation of the motion of smooth bodies in a viscous fluid by means of internal mechanisms was carried out, for example, in [9,10].…”
Section: Introductionmentioning
confidence: 99%